The contribution of mentors to support beginning teachers: The case of primary schools - Dagnew, Asrat (International Journal of Psychosocial Rehabilitation, 2024)
The purpose of this study was to assess the contribution and responsibilities of mentors in supporting beginning teachers in primary schools. Its’ internal consistency was 0.85.Mentors, beginning teacher, and principal respondents were selected randomly to fill out the questionnaire properly. Data gathered from 33 mentors, 63 beginning teachers, and 14 principals were analyzed and interpreted. Furthermore, portfolio of beginning teachers and information obtained through observation were incorporated. The findings of the study indicated that mentors did not support fresh teachers effectively, although mentors seem good in knowing their contribution and responsibilities. Absence of training, shortage of time and logistic, lack of interest, little number of experienced teachers in remote schools and absence of planned regular meeting were identified as crucial factors that affect mentoring relationship. The relationship between mentors and beginning teachers was found good. Accommodating students’ difference, in- effective evaluation, and absence of well developed content knowledge were identified as problem facing the novice teachers. Providing mentoring training, encouraging experienced teachers to retain in the remote schools for longer years, appropriate support by district expert and sharing experience from experienced teachers are some of the possible solutions.